Analysis of Speech Acts in Conversations Between Characters in the Film “Good Will Hunting (1997)” - Aulia, Maqdis Fayza; Syathroh, Isry Laila (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
Language is a crucial component of communication and serves as the foundation for interactions. In linguistics, there is a branch called pragmatics that studies speech acts. Pragmatics provides a framework for analyzing the relationship between language and context. Related to pragmatics, this research explores the classifications of speech acts in the film "Good Will Hunting (1997)”. This research aims to analyze the type of speech acts, as proposed by Searle (1976), that can be found in conversations between the characters Will Hunting and Sean Maguire. The film offers a narrative canvas to investigate representatives, directives, commissives, expressives, and declaratives. A descriptive qualitative method was employed in this research. The data was collected by employing attentive listening and note-taking methods and analyzed using descriptive and interpretative techniques. The findings of this research reveal a total of 61 speech acts, with representatives being the most dominant type with a total of 43 speeches, followed by directives totaling 8 speeches, 6 expressives, and both commissives and declaratives totaling 2 speeches each. The implications of these findings extend to a nuanced understanding of interpersonal communication in cinematic contexts. Keywords : pragmatics, speech acts, illocutionary acts